Epidemiological investigation and typing of Candida glabrata clinical isolates by FTIR spectroscopy - Essendoubi, Mohammed; Toubas, Dominique; Lepouse, Claire; Leon, Alain; Bourgeade, Fabienne; Pinon, Jean-Michel; Manfait, Michel; Sockalingum, Ganesh D. (Journal of microbiological methods, 2007)
Candida glabrata has emerged as one of the leading agents of fungal infections and strain typing is essential for epidemiological investigation that is generally achieved by molecular techniques. In this work, we studied twenty-nine C. glabrata strains isolated from different patients, using a phenotypic approach based on Fourier Transform Infrared (FTIR) spectroscopy, which has been in a previous study successfully applied as a rapid typing method for Candida albicans. A two-step procedure was used for the analysis. The first step included sixteen strains for the internal validation phase, which aimed at finding the spectral windows that would provide the best differentiation between strains. In this phase, hierarchical cluster analysis (HCA) carried out using three spectral windows (900–1200, 1540–1800, 2800–3000 cm − 1 ) allowed to obtain the best classification, where each patient strains could be clustered together. A genotypic technique based on randomly amplified polymorphic DNA-analysis (RAPD) confirmed these results. In a second step, the external validation phase, thirteen other clinical strains of C. glabrata isolated from multiple sites in four ICU patients, were tested by FTIR spectroscopy. The analysis was based on the spectral regions previously found in the first step. HCA classification of the strains gave four groups, one group per patient. These results suggest that no inter-human transmission took place. This study shows the potential of FTIR approach for typing of C. glabrata with several advantages compared to other techniques. FTIR typing is fast, effective, and reagent free. Moreover, it is applicable to all micro-organisms and requires a small quantity of biomass.